Computational modeling of cadmium sulfide deposition in the CdS/CdTe solar cell manufacturing process - Hemenway, Davis Robert, author; Sakurai, Hiroshi, advisor; Sampath, Walajabad, committee member; Sites, James, committee member (Colorado State University. Libraries, 2013)
A thin film CdS/CdTe solar cell manufacturing line has been developed in the Photovoltaic Materials Engineering Lab at Colorado State University. This system incorporates multiple stations using NiCr embedded heaters in graphite crucibles to successively sublimate layers of different photovoltaic materials onto glass substrates. Times, temperatures and chemical compositions of these layers can be varied or excluded according to the desired characteristics of the 3" x 3" solar cell sample. Though the tool allows for flexibility and variability of materials, the uniformity of material deposition remains one of the largest sources of performance variability between samples. Computational Fluid Dynamics (CFD) programs have been used previously to predict the thermal performance of the embedded heaters and to ensure thermal uniformity in each of the heated deposition pockets. The thermal modeling used in the designing of these sources has been proven to be within 2.5% of the experimentally measured temperatures in laboratory and industrial applications. Building off of the thermal modeling effort, CFD models were created to model the sublimation, vapor transport and film deposition that occurs within the CdS source. Fluid models of the CdS source were created to accurately reflect the current deposition technique with the intent of predicting future deposition uniformity during the evaluation process for new source designs. The developed model was able to accurately predict film growth in an untested source in which the uniformity of the film deposition was increased by over 70%. These models were created using ANSYS Fluent, and utilized Arrhenius reaction rate equations to describe the sublimation and condensation reactions. Modeling results showed a strong correlation with the experimental data.
Keywords: CdS; close-space sublimation; CFD; CdTe